2021
DOI: 10.3390/nu13103317
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and the Risk of Communicable Diseases

Abstract: The body of knowledge on alcohol use and communicable diseases has been growing in recent years. Using a narrative review approach, this paper discusses alcohol’s role in the acquisition of and treatment outcomes from four different communicable diseases: these include three conditions included in comparative risk assessments to date—Human Immunodeficiency Virus (HIV)/AIDS, tuberculosis (TB), and lower respiratory infections/pneumonia—as well as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 190 publications
(254 reference statements)
0
21
0
1
Order By: Relevance
“… Für Infektionskrankheiten (humane Immundefizienzviruskrankheit (HIV), ICD-10: B20–B24; Tuberkulose, ICD-10: A15–A19, B90; sowie für Infekte der unteren Atemwege, ICD-10: J09–22, P23, U04) wurden ausschließlich vermeidbare Krankheitsfälle, jedoch keine vermeidbaren Todesfälle modelliert. Diese Entscheidung wurde getroffen, da sich der unmittelbare Einfluss von Änderungen im Alkoholkonsum bei der Entstehung von Infektionskrankheiten besser quantifizieren lässt als für Todesfälle [ 25 ]. Es standen keine Daten zur Inzidenz von Hypertonie zur Verfügung, weshalb ausschließlich die vermeidbare alkoholbedingte Mortalität geschätzt wurde.…”
Section: Methodikunclassified
“… Für Infektionskrankheiten (humane Immundefizienzviruskrankheit (HIV), ICD-10: B20–B24; Tuberkulose, ICD-10: A15–A19, B90; sowie für Infekte der unteren Atemwege, ICD-10: J09–22, P23, U04) wurden ausschließlich vermeidbare Krankheitsfälle, jedoch keine vermeidbaren Todesfälle modelliert. Diese Entscheidung wurde getroffen, da sich der unmittelbare Einfluss von Änderungen im Alkoholkonsum bei der Entstehung von Infektionskrankheiten besser quantifizieren lässt als für Todesfälle [ 25 ]. Es standen keine Daten zur Inzidenz von Hypertonie zur Verfügung, weshalb ausschließlich die vermeidbare alkoholbedingte Mortalität geschätzt wurde.…”
Section: Methodikunclassified
“…The mechanism by which alcohol consumption increases the risk of pneumonia is through weakening the immune system and increasing the host's susceptibility to infection [3]. The causal pathways leading to alcohol-attributable pneumonia via compromised immunity are numerous and primarily target the key immune cells involved in combatting respiratory conditions, known as neutrophils, lymphocytes, macrophages, and other cells inherently responsible for immune responses [3]. A meta-analysis by Simou et al [7] found that the risk of community-acquired pneumonia significantly increased in people who consumed alcohol compared to those who did not (relative risk (RR) = 1.61, 95% confidence interval (CI) 1.25 to 2.08), and that for every 10-20 g higher alcohol intake per day, the risk of community-acquired pneumonia increased by 8% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia, as defined by the World Health Organization (WHO), is a form of respiratory infection that causes inflammation in the lungs, limits oxygen intake and consequently makes breathing difficult [ 1 ]. Pneumonia, together with other lower respiratory infections, was considered the fourth leading cause of death worldwide in 2019 [ 2 ] and had a significant overall disease burden, with an estimated 2.5 million deaths globally and approximately 97 million disability-adjusted life years (DALYs) [ 3 ]. It is estimated that in Europe in 2003, the cost of pneumonia was approximately ten billion euros annually, with the indirect cost due to lost productivity accounting for 3.6 billion euros [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases the risk of a range of communicable diseases, including HIV, TB, pneumonia, and COVID-19 infection [9]; and • May or may not increase the risk of overweight and obesity [10].…”
mentioning
confidence: 99%